Socio-economic effects of São Francisco Inter-basin Water Transfer on the low-income population - LIMA, Vitória Roberta Martins de Melo Galindo de (2021)
Exploring the effects of water supply promoted by the São Francisco Inter-basin Water Transfer (PISF) on socio-economic aspects is relevant for three main reasons. First, water is crucial for the local development. Second, there was a large volume of resources employed. Finally, many people were affected by the project. For filling a literature gap, this research proposes to verify those impacts on the low-income population living in municipalities that received water from PISF in 2017. To reach this purpose, we applied the Differences in Differences identification method for three different control groups, considering 2016 as the year before treatment and 2018 as the year after treatment. We investigated the effects on individual income, on whether the person had a paid work or not, on family income, and the participation in the Bolsa Família Program. The main results imply that, in the short term, the project has generally played a positive role in low-income population lives. However, the observed improvement on the analyzed variables does not necessarily mean an increment in family well-being.